Circular economy indicators applied to wastewater treatment process - Ion, Nicolae; Safta, Carmen-Anca (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
The present paper presents the results obtained for the evaluation of the circularity index using a methodology existing in the literature. The evaluation methodology of the technological process in the conceptual circular economy is based on the 3R principle (Reuse, Reduce, and Recycle) and it uses the life cycle analysis - LCA, and material flow analysis - MFA. The circularity indices are calculated for a wastewater treatment plant WWTP (Constanta Nord WWTP). Four possible scenarios were considered in which the economic circularity concept was hypothetical applied, for different materials and energy in the technological circuit of the sewage treatment plant. The four scenarios considered are in accordance with hypothetical situations of the technological development of the wastewater treatment plant. Thus, "Scenario 4" in which: the technology used would allow the drying of the sewage sludge and it's recycling, the fermentation of the sludge and the obtaining of biogas, the use of energy from renewable energy sources and the reuse of purified water in human activities, the circularity index is 88%. Compared to "Scenario 1" with circularity indicators quite close to those of "Scenario 4", but without a tertiary water treatment technology at the exit from the treatment plant for drinking water, the circularity index is increased in "Scenario 4" with 25%.